Wear progress and mechanisms in high temperature sieves. (March 2016) - Varga, M.; Widder, L.; Griesinger, M.; Adam, K.; Badisch, E.
Abstract: Sieves for high temperature (HT) environment are necessary for screening of iron oxide sinter in steel industry. Sinter is produced at temperatures of 1000 °C, crushed and screened for usage as raw material in blast furnaces. To determine the critical cause that leads to sieve cavity widening and subsequent productivity loss of the steel plant, a comprehensive damage analysis was undertaken. Sieves are equipped with plates covered by a hypereutectic hardfacing for wear protection. Cavities are cut by oxygen plasma cutting. Long-term wear investigation was done using replica samples taken from cavities after defined time intervals during the sieve's lifetime. Thereby differences in wear progress due to asymmetric material flow, position and alignment of cavities were studied. Additional temperature measurements were conducted via thermography of the sieve while in operation to identify service temperatures. Furthermore cross-sectional and microscopic analyses were carried out after end-of-life of the sieve to investigate wear mechanisms and microstructural changes. It was found that plasma cutting of the sieve cavities leads to a wide range of cavity widths. Continuous investigation of wear progress showed that the first interval resulted in significant blunting of edges. After this period of running-in, the ongoing wear loss at the edges became less pronounced. Significant wear was found descending up to 1.5 mm in depth along the cavity sidewalls. Furthermore, large break-outs could occur at any time due to cracks in the microstructure and fatigue. Nevertheless, blunting and cavity widening limited the lifetime of the sieve. Wear losses were more distinct on top of the sieve at the beginning of the sinter flow. No significant influence of the angle of the cavity positions in respect to the material flow was found. Cross-sections showed microstructural changes due to the thermal cutting process. Microstructure changed from hard hypereutectic structure to softer hypoeutectic microstructure, which is less wear resistant. Highlights: High temperature sieves operate at 250 °C with maxima of 600 °C. Running-in wear and blunting of cavity's edges are pronounced. Break-outs can occur at any time due to the inhomogeneous microstructure. Thermal cutting of sieve cavities is detrimental regarding wear resistance.